Virtual reality exposure therapy for reducing social anxiety associated with stuttering: the role of outcome expectancy, therapeutic alliance, presence and social presence - Chard, Ian; Van Zalk, Nejra; Picinali, Lorenzo (Frontiers in Virtual Reality, 2023)
Although several trials have demonstrated the effectiveness of Virtual Reality Exposure Therapy (VRET) for reducing social anxiety, there is little understanding about the factors that lead to symptom reduction across different treatment designs. Such factors may include outcome expectancy, therapeutic alliance, presence (perception of being in the virtual environment) and social presence (perception of interacting with others). We report on findings from a pilot trial of VRET targeting social anxiety in people who stutter, and examine the association of these four factors with treatment outcome. People who stutter reporting heightened social anxiety (n = 22) took part in the trial after being recruited via online adverts. Remotely delivered VRET was administered to participants in three sessions across three weeks. Each session targeted both performative and interactive anxiety. A virtual therapist helped participants to engage with treatment strategies, whilst also guiding them through exercises. Findings showed that presence and social presence were both negatively related to changes in fear of negative evaluation between pre- and post-treatment. However, presence, outcome expectancy and therapeutic alliance were positively related to changes in social anxiety symptoms. Furthermore, outcome expectancy and therapeutic alliance were quadratically related to fear of negative evaluation change. Nevertheless, the effect of presence on social anxiety, and the effects of presence and therapeutic alliance on fear of negative evaluation must be interpreted with caution as these were not large enough to reach sufficient statistical power. Therapeutic alliance did not mediate the relationship between outcome expectancy and treatment outcome. These findings suggest that the current VRET protocol affected social anxiety and fear of negative evaluation differently. We discuss how presence may underlie these mixed associations. We also suggest that the unexpected positive effects on social anxiety symptoms may have resulted from insufficient treatment strategies which inadvertently encouraged maladaptive learning.